Proposta de metodologia de avaliação de impactos ambientais (aia) para empreendimentos de energia eólica - Lima, João Pedro Machado de (2022)
The wind source represents the second main source explored for energy generation in Brazil, featuring more than 800 parks spread across twelve states of the national territory. the territory cearense, for the year 2022, already has a granted power of 2,506.4 MW, distributed by 99 parks. With the rise of the implementation of these projects in Brazil, there is the growth of impacts generated. Among the strategies to manage this scenario of generation of impacts, highlighting the Environmental Impact Assessment (AIA). In that sense, the present The objective of this work was to propose a methodology for assessing environmental impacts specific for energy generating projects based on wind power. For such, there was a survey of the scenario of renewable energies in Brazil and Ceará, based on bibliographic research, as well as data collection on Environmental Impact Studies (EIAs) of wind farms already approved in Ceará. The primary data source was the Ceará State Superintendence for the Environment (SEMACE) website, where a sample space of 84 approved EIAs was identified, and this study was prepared based on 41 of them, which are included in the period from 1997 to 2022. In addition, it was noticed that the environmental consulting market, in Ceará, presents diversity of active companies, among which few differ in terms of quantity of studies of large wind farms. In terms of methodology, there were preference for Checklist and Sequential List of Causes and Effects methods associated with other methods, such as the Leopold Matrix and Ad hoc. In the proposed method (Lima Method), the attributes were divided into three levels of order, in order to calculate the importance and magnitude. When interrelated with the character, there was a definition of significance, which was divided into five classes. The method was elaborated and validated against five others, demonstrating to be more rigorous in the evaluation process. It was also indicated that the methodology proposal showed less subjectivity compared to the others, due to the fact that the authors of the AIA will only interfere with the first order attributes, with subjectivity being decreased until reaching final significance.